Study of antimicrobial activity of Thymus vulgaris extract Against bacterial acne vulgaris. - Sura S Talib (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2024)
One of the most significant species in the Lamiaceae family, thymus vulgaris isendemic to the Mediterranean region and is used widely for both medicinal andculinary purposes. this study aims to evaluate the use of natural antimicrobials asan alternative therapy because the long-term use of antibiotics in the treatment ofacne has resulted in the formation of resistance. It may be inferred that Thymusvulgaris (T. vulgaris) extracts have the ability to suppress the test bacteria in theplan, indicating that they may be used as antimicrobial agents against pathogenicbacteria.